Perceived service quality, customer satisfaction and behavioural intentions towards hospitals in Sabah - Sidah Idris; Mohd Firdaus Mohd Hayati (Zes Rokman Resources, 2021)
Health system in Malaysia including hospitals, clinic and community health agencies can be very different from other work environments. Healthcare systems are complex and there are many things we need to know about types of hospital systems, patient care, insurance, healthcare providers and legal issues. This study aimed to examine the relationship among perceived service quality, customer satisfaction and behavioural intentions in the context of hospitals in Sabah, Malaysia. Information from 208 respondents were used through questionnaires for the purposed statistical data analysis using SmartPLS. The result showed only tangibles and empathy supports behavioural intentions in relations to health service providers in Sabah. This study tested relationships of tangibles, assurance and empathy with customer satisfactions respectively were shown to be significantly positive as well. Positive relationship between customer satisfaction and behavioural intentions was also observed in this study. As for the mediation analysis, the outcome indicated that tangibles, assurance and empathy respectively have indirect relationship with behavioural intentions mediated by customer satisfaction. Additional findings also showed that, while the direct effects of empathy on behavioural intentions was significant, the indirect impact was noted to be greater for behavioural intentions in connection with customer satisfaction as mediation. The result also showed that relative to other perceived service quality, empathy has the most impact on customer satisfaction as well as behavioural intentions respectively. The findings from this study significant to this industry which contribute to policy makers, service providers and other stakeholders.